Estudo químico do saibro coletado na região metropolitana do Recife para utilização nas argamassas de assentamento e revestimento de alvenaria. - Paiva, Sérgio Carvalho de (2008)
The mortars used in many parts of Brazil to set blocks or to cover masonry are normally prepared with cement and sand with clay minerais additions, called "saibro" or "arenoso" (a clayey sand). These additions provide workability, water retention and plasticity to the mortars, similarly as in the mixed mortars (cement, sand and lime). The properties of "saibro" are poorly known, in spite of its large use. Therefore, the choice of "saibro" to use in mortars has been empirical, and the mortars quality is not guaranteed, what may cause some pathology in the masonry covers. The objective of this work was to analyze "saibro" samples to be used in cement and "saibro"mortars (CSM). Sixty two samples of "saibro" were collected from 24 ofthe most commercially explored fields in the Recife's Metropolitan Area. Chemical "saibro" characterization tests, with 21 determinations, were applied to ali samples. A quality index of "saibro" for mortars (QISM) was proposed and nine samples of "saibro" were selected to be used in mortars. Chemical analysis for fresh mortars and mechanical tests for the hardened ones were provided for two different compositions. The results were statistically analyzed by principal components analysis (PCA). The chemical characterization tests showed that the best "saibros" for masonry mortars were collected in the northern part of the studied region. The "saibro" maio chemical characteristics that influenced positively the quality of the CSM were: pH, Cations Exchange Capacity (CEC < 27 cmoic kg-1), Surface Area (SA < 102 m2g-1), Silicon Oxide Percentage and Water Percentage in the Saturation Extract. The physical and chemical indicators are fundamental to qualify the mortars performance.